Final Position Arbitration and Intertemporal Compromise - Dworkin, James B. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1977)
This paper seeks to present further evidence from the realm of professional baseball in regard to Swimmer's criticism of final offer procecure.